“Dig, What Makes Your Mouth So Big?”: Off-Modern Nostalgia, Symbolic Cannibalism, and Crossing the Border of the Universal Language in Clarence Major’s “The Slave Trade: View from the Middle Passage” - Kamionowski, Jerzy (Studia Anglica Posnaniensia, 2017)
African American literature on the Middle Passage has always challenged white supremacy’s language with its power to define and control. This article demonstrates how the border of such a “Universal Language” is challenged and trespassed in Clarence Major’s ekphrastic poem “The Slave Trade: View from the Middle Passage” in order to communicate – through the implementation of the voice of a disembodied water spirit Mfu – the black perspective on understanding the slave trade and effectively resist the symbolic cannibalism of Western Culture. The trope of antropophagy often appears in Middle Passage poems in the context of (mis)communication (which results in the production of controlling, racist images of blacks) and stands as a sign of Euro-American power to create the historical, hierarchical, racial reality of the Atlantic slave trade in its economic and symbolic dimensions. The strategy implemented by Major in his poetic confrontation with representation of historical slave trade in European and American Fine arts may be classified as “off-modern” (to use Svetlana Boym’s (2001) nomenclature), which immediately places his poem in a “tradition of critical reflection on the modern condition that incorporates nostalgia” as a means of a critical analysis of the heritage and limitations of a given culture. My claim is that the poem’s “off-modern nostalgia” perspective is a version of textualist strategy which Henry Louis Gates (1988)identifies as Signifyin(g). Major/Mfu successfully perforates and destabilizes the assumed objectivity and neutrality of the images of blacks and blackness created and circulated within the realm of the visual arts of the dominant Western Culture. In “The Slave Trade: View from the Middle Passage” Signifyin(g) takes the form of what could be called an ekphrastic (re)interpretation of actual works of art and joins in the critique of essentialist views often associated with understanding of meaning.